γGT and PCSK9 variants in subjects with hyper-LDL-cholesterolemia - Kotani, Kazuhiko; Hamasaki, Masato; Kapse, Snehal (Acta bio-medica : Atenei Parmensis, 2022)
Gain-of-function (GOF) variants of proprotein convertase subtilisin/kexin type 9 (PCSK9) gene cause high blood low-density lipoprotein (LDL) cholesterol and PCSK9 levels, which are respectively the markers of cardiovascular disease (CVD). High blood activity of gamma-glutamyl transpeptidase (γGT), a pro-oxidant induced by oxidative conditions, is also a marker of CVD. There may be an association between γGT and PCSK9 variants. We aimed to examine the γGT activity by a GOF variant, p.E32K, of PCSK9 in subjects with hyper-LDL-cholesterolemia, an at-risk state for CVD. This study enrolled 114 subjects (mean age, 59 years; 38 males) with hyper-LDL-cholesterolemia who underwent a genotype assay for identification of p.E32K variant and enzymatic measurement of γGT activity. The relationship between the γGT activity and p.E32K was analyzed. γGT activity was significantly lower (median, 21 IU/L) in subjects with p.E32K (n = 12) than in those without the variant (30 IU/L, P < 0.05). The results remained confirmed by multivariate-adjusted analysis. An inverse association was found between γGT and p.E32K, a GOF variant. Elucidation of the mechanism for their association may help understand the development of CVD by PCSK9 variants.